Perancangan Sistem Ringkasan Materi Perkuliahan Menggunakan Artificial Intelligence Berbasis Web - Edwin Prayoga H; Ahmad Nugroho (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
The world of education has undergone major changes since the advent of technology and the internet. Most students prefer new learning methods brought by technology rather than listening and writing in class which are considered outdated. The presence of technology such as Artificial Intelligence (AI) should be able to overcome the weakness of conventional learning methods and make it more interesting for students. Conventional learning activities in class such as writing and taking notes can be replaced by AI which is designed to perform tasks like humans. Therefore, this study was conducted by developing a system for recording and summarizing lectures using AI technology. The system development process uses the waterfall method as a guide, while the system modeling is created using the UML method. The application of AI technology into conventional learning methods can create a more interactive class by setting aside student's tasks like writing and taking notes, creating more interaction with the lecturer, resulting in a higher quality of education.